Mykola Markevych’s “Ukrainian Melodies”: Between Thomas Moore and Afanasy Fet - Ляпина, Лариса (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The aim of the article is to analyze the poetics of Mykola Markevych’s main book of lyric poems (Ukrainskiia melodii, 1831). It belongs to a particular neo-genre called melody, which formed its own tradition. Its beginnings are connected with the followers of Thomas Moore and George Byron, while its climax in the Russian poetry came with Afanasy Fet’s Melodies. Within this genre Markevych formed an interesting folk-ballad type of melody, using special versifying methods; he made his texts both rhythmical and expressive and gave his book a complex unified composition.